Botany, ethnopharmacology, phytochemistry and pharmacology of Erodii Herba Geranii Herba-An review. (10th February 2023) - Kong, Chuchu; Pang, Xinxin; Su, Zhijun; Liu, Yonggang
Abstract: Ethnopharmacological relevance: As a commonly used traditional Chinese herbal medicine, Erodii Herba Geranii Herba ( Geranium wilfordii Maxim., Geranium carolinianum L. and Erodium stephanianum Willd.), which was known as Laoguancao (Chinese:老鹳草), has high medicinal value. It has been used to dispel rheumatism, dredge the meridians, activate blood circulation, remove blood stasis, clear heat and detoxify, and stop diarrhea and dysentery. It's also used to treat eczema, sores, carbuncles, boils caused by accumulation of damp toxin. Aim of the review: This review aimed to provide a systematic and comprehensive analysis of the current research progress in terms of the botany, ethnopharmacology, phytochemistry and pharmacological activities of Erodii Herba Geranii Herba, and discuss expectations for prospective research and implementation about this herb. Materials and methods: Information on Erodii Herba Geranii Herba was gathered via the Internet (using Google Scholar, Baidu Scholar, Pubmed, Elsevier, ACS, Medline Plus, CNKI and Web of Science) and libraries. Additionally, information was also obtained from local books and brilliant scholars in ethnopharmacology. Results: More than isolated 240 chemical compounds were recorded, and main compositions are tannins, flavones, organic acids and volatile oil. The pharmacoactives of Erodii Herba Geranii Herba and its active constituents are diverse, including antibacterial, antiviral, antioxidant, liver and kidney protection, anti-inflammatory and analgesic, other activities. Among them, the antibacterial, antiviral, anti-inflammatory, analgesic, antidiarrheal and other pharmacological activities of it are consistent with traditional applications. Conclusions: All kinds of research conducted on Erodii Herba Geranii Herba, especially in field of ethnopharmacological use, phytochemicals and pharmacology have been reviewed. There are plenty of active compounds with varied effects in Erodii Herba Geranii Herba. However, some traditional applications and pharmacological activities of Erodii Herba Geranii Herba have not been scientifically evaluated or convincing due to incomplete methods and ambiguous results, as well as the lack of clinical data. In order to verify the pharmacological activity, clinical efficacy and safety of it, a systematic and comprehensive research evaluation is also required. As an important traditional Chinese medicine, Erodii Herba Geranii Herba should be further explored to promote the development of new drugs and therapeutics for various diseases. How to make better use of it should be paid more attention to. Graphical abstract: Image 1